DEVELOPING A UNIVERSITY LEARNING QUALITY ASSESSMENT SCALE - Habiche Bachir; Bakhta Chettouh (International Journal of Innovative Technologies in Social Science, 2025)
The current study aimed to attempt to construct a scale for evaluating and assessing the quality of education from the perspective of university professors. In the theoretical framework of the construction, we relied on Item Response Theory (IRT), which is considered the modern theory used in scale development. The study found the following: • The data fit the Rasch model. • The scale demonstrated acceptable validity. • The scale exhibited high reliability. Based on the findings of the current study, it becomes evident that there is a necessity to employ modern measurement theory and its various models to achieve the highest possible level of objectivity in psychological and educational measurement.